An Evaluation Method for the Skeleton Model Based on Function–Behavior–Structure Correlation Analysis - Sichao Liu; Shaoke Nan; Ling Tian (Machines)
The skeleton model is an essential tool to support the top-down design of complex products, and the rationality of its design has a significant influence on the detailed design of products. However, the current skeleton models of complex products are mainly designed based on experience, and there is no practical method to judge the rationality of the skeleton model design. This study conducts a component correlation analysis of the skeleton model of complex products. It proposes a method for clustering analysis and evaluating multi-level skeleton models based on the transitive closure method. The effectiveness of the method is verified through a case study of a rocket nose cone’s skeleton model. This method provides a scientific analysis method for designers to establish a reasonable skeleton model. In addition, the knowledge description of the skeleton model established in this study lacks sufficient flexibility, and the time complexity of cluster analysis needs to be reduced.